The IL-17/IL-23 Axis and Its Genetic Contribution to Psoriatic Arthritis - Vecellio, Matteo; Hake, Vivien Xanath; Davidson, Connor; Carena, Maria Cristina; Wordsworth, B. Paul; Selmi, Carlo (Frontiers in Immunology, 2021)
Psoriatic arthritis (PsA) is a chronic inflammatory disease belonging to the family of spondyloarthropathies (SpA). PsA commonly aggravates psoriasis of the skin and fre-quently manifests as an oligoarthritis with axial skeletal involvement and extraarticular manifestations including dactylitis, enthesitis and uveitis. The weight of genetic predisposition to psoriasis and PsA is illustrated by the concord-ance rates in monozygotic twins which clearly demonstrate that genomics is insufficient to induce the clinical phenotype. The association of PsA with several single nucleotide polymorphisms (SNPs) at the IL23R locus and the involvement of Th17 cells in the im-munopathogenesis of PsA clearly put the IL-23/IL-17 axis in the spotlight. The IL-23 and IL-17 cytokines have a pivotal role in the chronic inflammation of the synovium in PsA and are also prominent in the skin lesions of those with PsA. In this review, we focus on the genetic association of the IL-23/IL-17 axis with PsA and the contribution of these master cytokines in the pathophysiology of the disease, high-lighting the main cell types incriminated in PsA and their specific role in the peripheral blood, lesional skin and joints of patients. We then provide an overview of the approved biologic drugs targeting the IL-23/IL-17 axis and discuss the advantages of genetic stratification to enhance personalised therapies in PsA.